2021
DOI: 10.1111/1467-8551.12546
|View full text |Cite
|
Sign up to set email alerts
|

Stratified View of Institutional Fit

Abstract: Institutional theory suggests that organizations pursue legitimacy by institutional fit. However, there is a debate about the relationship between institutional fit and performance. Thus, the goal of the present study is to delve more deeply into this issue. Specifically, we evaluate how three dimensions of fit (technology, structure and culture) are related to organizational performance. The analysis is based on survey data and secondary archival data from a sample of 200 firms. Results show that the associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 89 publications
0
3
0
Order By: Relevance
“…Fernandez-Giordano et al. (2022) show that different dimensions of institutional fit (technological, strategic and cultural fit) produce different performance consequences.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Fernandez-Giordano et al. (2022) show that different dimensions of institutional fit (technological, strategic and cultural fit) produce different performance consequences.…”
Section: Introductionmentioning
confidence: 96%
“…Durand and Haans (2022) discussed optimal distinctiveness through the lens of organizational ability to pursue similar or distinct strategies but without reference to the institutional context. JSMA 16,2 Fernandez-Giordano et al (2022) show that different dimensions of institutional fit (technological, strategic and cultural fit) produce different performance consequences. They found a positive correlation between institutional fit and performance on the technological dimension.…”
Section: Introductionmentioning
confidence: 99%
“…biasing the school's financial reports. Addressing the challenges ofFernandez-Giordano et al (2022) andUtomo (2021) this study demonstrates that among the empirically identified organizational response strategies, the use of adaptation management can be identified as a new response strategy. The findings indicate that the observed organizations develop or maintain certain impressions to avoid direct rejection of controversial requests while simultaneously making them irrelevant.…”
mentioning
confidence: 93%